Incorporating Social and Environmental Aspects in the Economic Dimension of the Triple Bottom Line Tool to Sustain Manufacturing SMEs in South Africa - Qeke , Siphesande R.; Dubihlela, J. (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
To align with what the world has envisioned for 2030 requires a view of opportunities available, whilst also recognising the risks and challenges. It is almost less than a decade to realise the progress made to the envisioned agenda that has been put forward by the Global Goals, informing our world to be a radically better place in 2030. In the midst of transforming and adapting to the novel future, it is hard to ignore the fact that the past century has witnessed environmental destruction on an unprecedented scale. Not only has it affected progress to the envisioned 2030, however, it has compromised the ability of the future generations to benefit from the natural resources offered by a planet earth, and has triggered sustainability question which awarded everyone a role to play. Small and medium manufacturing firms in South Africa has progressed to operate within the lenses of sustainability by reporting, accounting and taking responsibility of incorporating social and environmental concerns into their operations as a result of the growing prominence of the triple bottom line (TBL) framework. Stemming from the results, of a quantitative research that was designed to purposively select the sample of 200 respondents which were considered as decision makers of manufacturing SMEs in South Africa. The revelation shown that manufacturing SMEs' thrust for profitability at the expense of sustainability threaten efforts to induce enormous positive business outcomes, and leverage on future business performance and sustainability and at the same time it corrodes their potential leverage for competitiveness. This served as a lesson for businesses to change their ways of operating and called for policy markers’ interventions to devote the policies and frameworks to guide SMEs out of their peril, and further contributes to their derailed progress of attaining sustainability.